Integrated Proteomic and Transcriptomic Analyses Reveal the Roles of Brucella Homolog of BAX Inhibitor 1 in Cell Division and Membrane Homeostasis of Brucella suis S2 - Zhang, Guangdong; Zhong, Fangli; Chen, Lei; Qin, Peipei; Li, Junmei; Zhi, Feijie; Tian, Lulu; Zhou, Dong; Lin, Pengfei; Chen, Huatao; Tang, Keqiong; Liu, Wei; et al. (Frontiers in Microbiology, 2021)
BAX inhibitor 1 (BI-1) is an evolutionarily conserved transmembrane protein first identified in a screening process for human proteins that suppress BAX-induced apoptosis in yeast cells. Eukaryotic BI-1 is a cytoprotective protein that suppresses cell death induced by multiple stimuli in eukaryotes. Brucella, the causative agent of brucellosis that threatens public health and animal husbandry, contains a conserved gene that encodes BI-1-like protein. To explore the role of the Brucella homologue of BI-1, BrBI, in Brucella suis S2, we constructed the brbI deletion mutant strain and its complemented strain. brbI deletion altered the membrane properties of Brucella suis S2 and decreased its resistance to acidic pH, H2O2, polymyxin B, and lincomycin. Additionally, deleting brbI led to defective growth, cell division, and viability in Brucella suis S2. We then revealed the effect of brbI deletion on the physiological characteristics of Brucella suis S2 via integrated transcriptomic and proteomic analyses. The integrated analysis showed that brbI deletion significantly affected the expression of multiple genes at the mRNA and/or protein levels. Specifically, the affected divisome proteins, FtsB, FtsI, FtsL, and FtsQ, may be the molecular basis of the impaired cell division of the brbI mutant strain, and the extensively affected membrane proteins and transporter-associated proteins were consistent with the phenotype of the membrane properties’ alterations of the brbI mutant strain. In conclusion, our results revealed that BrBI is a bacterial cytoprotective protein involved in membrane homeostasis, cell division, and stress resistance in Brucella suis S2.